A 10-Food Group Dietary Diversity Score Outperforms a 7-Food Group Score in Characterizing Seasonal Variability and Micronutrient Adequacy in Rural Zambian Children. Issue 1 (25th January 2018) - Caswell, Bess L; Talegawkar, Sameera A; Siamusantu, Ward; West, Keith P; Palmer, Amanda C
Abstract: Background: Dietary diversity scores and dichotomous indicators derived from them are widely used to assess dietary quality, and specific scoring methods have been recommended for women and 6- to 23-mo-old children. However, there is no specific score recommended for older children and the effect of seasonal dietary changes on score performance is not well documented. Objective: We assessed performance of 2 recommended dietary diversity scores as indicators of dietary quality over 3 seasons. Methods: We conducted 7 repeat 24-h dietary recalls among 4- to 8-y-old rural Zambian children ( n = 200) over 6 mo. Dietary diversity was assessed using a 7-food group score for assessing infant and young child feeding (DDS-IYCF) and a 10-food group score for use among women of reproductive age (DDS-W). Micronutrient intake adequacy was described by mean probability of adequacy (MPA) over 11 micronutrients. Longitudinal models were fit to test the association between each score and MPA overall and by season. Receiver operating characteristic (ROC) curves were used to describe indicator performance of each score. Results: Mean ± SE scores were 4.11 ± 0.03 for DDS-IYCF and 4.39 ± 0.03 for DDS-W. Both scores varied by season, but DDS-W better reflected seasonal dietary changes. Across seasons, MPA increased 1–6 percentage points/unit increase in DDS-IYCF or 1–10 percentage points for DDS-W ( P < 0.05). Score performance as a predictor of MPA > 0.75 was moderate, with area under the ROC curve values by season ranging from 0.63 to 0.77 for DDS-IYCF and from 0.66 to 0.72 for DDS-W. Conclusions: DDS-W performed better than DDS-IYCF in characterizing seasonal variability and micronutrient adequacy among rural Zambian children.